Over-expression of Runx1 transcription factor impairs the development of thymocytes from the double-negative to double-positive stages - Wong, W.F.; Nakazato, M.; Watanabe, T.; Kohu, K.; Ogata, T.; Yoshida, N.; Sotomaru, Y.; Ito, M.; Araki, K.; Telfer, J.; Fukumoto, M.; Suzuki, D.; et al. (Blackwell Publishing, 2010)
Runx1 transcription factor is highly expressed at a CD4/CD8-double-negative (DN) stage of thymocyte development but is down-regulated when cells proceed to the double-positive (DP) stage. In the present study, we examined whether the down-regulation of Runx1 is necessary for thymocyte differentiation from the DN to DP stage. When Runx1 was artificially over-expressed in thymocytes by Lck-driven Cre, the DN3 population was unaffected, as exemplified by proper pre-T-cell receptor expression, whereas the DN4 population was perturbed as shown by the decrease in the CD27hi sub-fraction. In parallel, the growth rate of DN4 cells was reduced by half, as measured by bromodeoxyuridine incorporation. These events impaired the transition of DN4 cells to the DP stage, resulting in the drastic reduction of the number of DP thymocytes. The Runx1 gene has two promoters, a proximal and a distal promoter; and, in thymocytes, endogenous Runx1 was mainly transcribed from the distal promoter. Interestingly, only distal, but not proximal, Runx1 over-expression exhibited an inhibitory effect on thymocyte differentiation, suggesting that the distal Runx1 protein may fulfil a unique function. Our collective results indicate that production of the distal Runx1 protein must be adequately down-regulated for thymocytes to transit from the DN to the DP stage, a critical step in the massive expansion of the T-cell lineage.